INNOVATIONS IN CONCCURENT FURNITURE ENGINEERING (Innovation in Woodworking Industry and Engineering design, 2026)
Basic aspects and innovations in concurrent engineering and its major place in the production of furniture in our days are represented. The main advantages and the main differences between concurrent and traditional furniture engineering are analyzed. Examples of using 2D and 3D models made by CAD-based programs in the production of furniture, with the help of CNC machines and 3D printers are considered. The new technology for 3D printing and its using for production of wood elements and furniture are presented, which leads to establishing the idea for „Smart wood materials”. The opportunities to use these technologies to make easier the work of designers and adapt them in everyday life, which make them more available to the customer are discussed.